The impact of cadmium exposure on breast cancer risk: Exploring dose-response relationships and mediating effects - Yongbin Lu; Yongxia Dang; Yilin Chen; Yizhuo Chen; Xu Hui; Xiaonan Li; Xin Fan; Jingru Yang; Xiaoling Ling; Li Ma; Zhiyuan Cheng; Kehu Yang (Ecotoxicology and Environmental Safety)
Cadmium (Cd), an endocrine disruptor, has been linked to hormone-related cancers, including breast cancer (BC). However, previous studies investigating the association between Cd exposure and BC risk have yielded inconsistent results, and the effects of Cd on BC subtypes remain poorly understood. We employed logistic regression and restricted cubic splines (RCS) to examine the relationship between Cd exposure and BC. A meta-analysis was subsequently conducted to validate the association between Cd exposure and BC. Lastly, mediation analysis was applied to explore the underlying mechanisms linking Cd exposure to BC. Data from 5954 participants in the National Health and Nutrition Examination Survey (1999–2020) were analyzed. Elevated Cd levels in the fourth quartile were significantly associated with an increased BC risk (odds ratio (OR) = 3.74, 95 % confidence interval (CI): 1.45 - 9.62, Ptrend = 0.019), compared to the first quartile group. A linear dose-response relationship was seen between urinary Cd levels and BC risk (Pnon-linear = 0.532), with BC risk increasing 317 % (OR = 3.17, 95 % CI: 1.93 - 5.20, Ptrend < 0.001) for 1 μg/g creatinine increases in urinary Cd levels. The meta-analysis, which included 20 eligible studies, further observed a possible link between Cd exposure and BC risk (relative risk (RR) = 1.17, 95 % CI: 1.06 - 1.29, I2 = 83 %), particularly in estrogen receptor-positive (ER+) subtypes (RR = 1.08, 95 % CI: 1.01 - 1.16, I2 = 70 %). Mediation analysis further revealed that glycated hemoglobin (HbA1c) mediated 9.09 % of the Cd-BC risk association. In conclusion, the study results suggest a potential association between Cd levels and an increased BC risk, particularly in ER+ subtypes. Mechanistically, HbA1c was identified as a mediator in this association. These findings underscore the complex interplay between Cd exposure and metabolic dysregulation in the development of BC, highlighting the potential role of HbA1c in modulating BC risk among individuals exposed to Cd.